"Lying‐Down" Adrenal Sign: There Are Exceptions to the Rule Among Fetuses and Neonates. (8th July 2017) - Majmudar, Anand; Cohen, Harris L.
Abstract : A linear‐shaped or "lying‐down" adrenal gland is a sign often seen with the absence of the kidney in the renal fossa due to renal agenesis, renal ectopia, or horseshoe kidney. It is theorized that the presence of the kidney in the normal location within the renal fossa is important for the formation of the normal triangular inverted V or Y adrenal shape. There are exceptions to this rule whereby a kidney is missing from the renal fossa, yet a normal adrenal shape is present. This series looked at 18 cases of an empty renal fossa in fetal, neonatal, and pediatric patients and recorded the shape of the adrenal gland. Nine cases (50%) appropriately showed the linear or lying‐down adrenal gland; 6 (33%) showed an exception to the rule, with a normally shaped adrenal gland; and 3 (17%) showed a pseudo exception in which the adrenal gland was linear but blended with the diaphragmatic crus to simulate a triangular adrenal gland. The sonographic characteristics of the crus are different from those of the adrenal gland; thus, this pseudo exception can be avoided by careful inspection. Because the absence of the kidney is often a difficult diagnosis, the lying‐down adrenal gland sign can be a helpful secondary sign for confirming that a kidney is absent or ectopic in position and not within the renal bed.